Microbiological and Nutritional Properties of Frankfurter-Type Fish Sausage - T, Nkrumah; WY, Akwetey (International Journal of Nutrition, 2018)
Fish meat is a common and broadly used food due to its high nutritional values yet the bones and flavour of fresh fish can be unpleasant. The unpleasant fishy flavour makes it difficult to handle and process. The fishy flavour is as a result of microbial presence and growth. Studies associated with microbial contaminations have concentrated more on the carcass. Such contaminations which affect the microbiological status of processed products can emanate from spices and other non-meat ingredients, environment, equipment and handlers. The successful application of processing/preservation technology results in the conservation of desirable qualities in stabilized and varietal fish products. This study sought to use fish in the manufacture of frankfurter-type sausages, which could have improved preservation characteristics without any adverse effects on sensory properties. The nutritional composition and microbiological safety of fresh fish and sausages were determined using the methods described by AOAC and ICMSF respectively. The study showed that, catfish sausages were higher in protein (15.69 %) and were lower in fat (10.66%) compared to the other sausages. Total Viable Counts (TVC) were within the accepted limits (106 and 107cfu/g) for fish and pork respectively. E. coli  was not detected in any of the treatments during frozen storage for 6 weeks. It was concluded that catfish frankfurter has high nutritive value because it contained less fat but with higher crude protein. Like pork frankfurters, both catfish and mackerel sausages could be stored for six weeks without any negative effects on microbial quality.
Keywords: Total Viable Count; Nutritional property; Fish frankurter